Shiva linga adorned with a metal naga image - Temples of India Project Team (Jio Institute, 2024)
The stone platform on the left side of the stairs, leading to the temple, has a group of five sculptures. The central sculpture is a Shiva linga adorned with a metal naga image, preceded by a Nandi sculpture. Flanking the linga are three additional pindi (stone) sculptures, probably representing members of Shiva parivara (family): Parvati on the right, and Kartikeya and Ganesha on the left.